Confinement of nano CdS in designated glass: a novel functionality of quantum dot-glass nanosystems in solar hydrogen production - Kale, Bharat B.; Baeg, Jin-Ook; Apte, Sanjay K.; Sonawane, Ravindra S.; Naik, Sonali D.; Patil, Kashinath R. (Journal of Materials Chemistry, 2007)
The present work is the investigation of our novel approach to designing quantum dot-glass nanosystems by confining nano CdS in designated glass and the first employment of such a quantum dot system in solar hydrogen production. The CdS quantum dots were grown in a special glass matrix, which involved a sequence of steps. The obtained glass was of uniformly bright yellow in color and the bulk glass was pulverized to a fine powder of micron size particles. The glass powder was characterized structurally and morphologically. X-Ray diffraction and electron diffraction patterns reveal a hexagonal crystallite system for the CdS quantum dots. Field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, X-ray fluorescence spectroscopy and chemical leaching with HCl studies demonstrate that the 2.5 nm size CdS quantum dots distribute homogeneously in a monodispersed form in the glass domain and on the surface with a ``partially embedded exposure'' configuration. This disposition imparts an excellent photostability against photocorrosion and also a facile catalytic function. Therefore, even a very small amount of CdS quantum dots (0.005 g per gram of glass powder) is able to photodecompose H2S under visible light (lambda >= 420 nm) both in alkaline and pure aqueous media and produce solar hydrogen with markedly high quantum yields of 17.5 and 11.4%, respectively at 470 nm. Salient features like reusability after simple washing, corrosionless-stability and remarkable catalytic activity of this quantum dot-glass nanosystem are brought forth by our novel catalyst design and are much acclaimed in large scale solar H-2 production.

N-doped TiO2 nanoparticle based visible light photocatalyst by modified peroxide sol-gel method - Jagadale, Tushar C.; Takale, Shrikant P.; Sonawane, Ravindra S.; Joshi, Hrushikesh M.; Patil, Shankar I.; Kale, Bharat B.; Ogale, Satishchandra B. (Journal of Physical Chemistry C, 2008)
The peroxide gel route is employed to synthesize N-doped TiO2 nanoparticles (NP) at low temperature using titanium tetraisopropoxide, ethylmethylamine, and hydrogen peroxide as precursors. Structural studies show anatase phase in the undoped titania NPs as well as at 5 at. % N-doped titania NPs, although with a degree of matrix disorder in the latter case. The annealing of N-doped titania NPs at different temperatures shows that above 400 degrees C nitrogen escapes the O-Ti-O matrix and at 500 degrees C the sample becomes crystalline. Transmission electron microscopy reveals that the particle size is in the range of 20-30 nm for the undoped TiO2 but only 5-10 nm for N-doped TiO2. At higher nitrogen concentration (10 at. %) bubble-like agglomerates form. FTIR and photoluminescence quenching also confirm the incorporation of nitrogen in anatase TiO2. Optical properties reveal an extended tailing of the absorption edge toward the visible region upon nitrogen doping. X-ray photoelectron spectroscopy is used to examine the electronic state of doped nitrogen and the associated possible electronic modification of the TiO2 matrix. Under visible light irradiation the undoped TiO2 NPs do not show any significant photocatalytic activity, as expected; however, the 5 at. % N-doped TiO2 NPs show excellent activity.

Ecofriendly hydrogen production from abundant hydrogen sulfide using solar light-driven hierarchical nanostructured ZnIn2S4 photocatalyst - Chaudhari, Nilima S.; Bhirud, Ashwini P.; Sonawane, Ravindra S.; Nikam, Latesh K.; Warule, Sambhaji S.; Rane, Vilas H.; Kale, Bharat B. (Green Chemistry, 2011)
It is quite well-known that refineries are producing huge amount of H2S which has been used to produce sulphur and water using the well-known Claus process. This process is not an economically viable process, due to the high-cost chemical process and creates further acute environmental problems. Therefore, we have demonstrated the conversion of poisonous H2S into H-2 using an ecofriendly phocatalysis process which is a green unconventional energy source. We have investigated ecofriendly nanostructured ZnIn2S4 photocatalyst to produce hydrogen from H2S using solar light. We also demonstrate the controlled synthesis of hierarchical nanostructured ZnIn2S4 using a facile hydrothermal method. The morphologies obtained have been greatly influenced by the presence of triethylamine (TEA) with various concentrations during the reaction. Surprisingly, a highly crystalline hexagonal layer structured ZnIn2S4 was obtained instead of cubic spinel. The hierarchical nanostructure, i.e. marigold flower-like morphology, was obtained without any surfactant. The thin and transparent petals self-assembled to form the unique nanostructured marigold flower. The highly crystalline puffy marigold flowers and nanoplates/nanostrips were obtained using TEA-assisted hydrothermal synthesis. Optical study shows the band gap in the range of 2.34-2.48 eV. Considering the band gap in the visible region, ZnIn2S4 is used as photocatalyst for hydrogen production from hydrogen sulphide under solar light which is hitherto unattempted. The constant photocatalytic activity of hydrogen evolution, i.e. 5287 mu mol h(-1), was obtained using such hierarchical nanostructured ZnIn2S4 under visible light irradiation. It is noteworthy that the H-2 evolution rate obtained is much higher compared to earlier reported photocatalysts. Considering the significance of morphologies for photocatalytic application, the formation mechanism has also been furnished. The unique hierarchical nanostructured ZnIn2S4 ternary semiconductor having hexagonal layer will have potential applications in solar cells, LEDs, charge storage, electrochemical recording, thermoelectricity and other prospective electronic and optical devices.

Novel solar light driven photocatalyst, zinc indium vanadate for photodegradation of aqueous phenol - Mahapure, Sonali A.; Rane, Vilas H.; Ambekar, Jalindar D.; Nikam, Latesh K.; Marimuthu, R.; Kulkarni, Milind V.; Kale, Bharat B. (Materials Research Bulletin, 2011)
In the present investigation, we have demonstrated the synthesis of novel photocatalyst, zinc indium vanadate (ZIV) by solid solid state route using respective oxides of zinc, indium and vanadium. This novel photocatalyst was characterized using XRD, FESEM, UV-DRS and FTIR in order to investigate its structural, morphological and optical properties. XRD clearly shows the formation of phase pure ZIV of triclinic crystal structure with good crystallinity. FESEM micrographs showed the clustered morphology having particle size between 0.5 and 1 mu m. Since, optical study showed the band gap around 2.8 eV, i.e. in visible region, we have performed the photocatalytic activity of phenol degradation under visible light irradiation. The photodecomposition of phenol by ZIV is studied for the first time and an excellent photocatalytic activity was obtained using this novel photocatalyst. Considering the band gap of zinc indium vanadate in visible region, it will also be the potential candidate for water splitting. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Chemical synthesis; Oxides; X-ray diffraction

Self assembled CdLa2S4 hexagon flowers, nanoprisms and nanowires: novel photocatalysts for solar hydrogen production - Kale, Bharat B.; Baeg, Jin-Ook; Kong, Ki-jeong; Moon, Sang-Jin; Nikam, Latesh K.; Patil, Kashinath R. (Journal of Materials Chemistry, 2011)
We report here a new ternary chalcogenide material, cadmium lanthanum sulfide (CdLa2S4) produced using a facile hydrothermal method at 433 K. The effect of the solvent on the morphology of the CdLa2S4 was demonstrated for the first time. The prima facie observations revealed the formation of highly crystalline hexagonal structures in the form of flowers in aqueous medium. The flowers comprise hexagonal columns similar to 300 nm in diameter and 1-1.2 mu m in length. All the hexagonal structures have a sharp tip with a cavity of 10 nm and are almost equal in size. The nanoprisms have an average base size of 35 nm with 35 nm edges, and the nanowires have a diameter of 10-15 nm; both were obtained in methanol. Crystal and electronic structure calculations were performed using the Vienna ab initio simulation package (VASP) based on density functional theory (DFT). Considering the band gap of pristine CdLa2S4 in the visible region (2.3 eV), we have demonstrated CdLa2S4 as a photocatalyst for the production of H-2 under solar light. Nanostructured CdLa2S4 prisms gave the maximum hydrogen production, i.e. 2552 mu mol h(-1). Being a stable ternary nanostructured metal sulfide (with nanohexagons, nanoprisms, nanowires), CdLa2S4 may have other potential prospective applications in solar cells and optoelectronic devices.

Eco-friendly, highly stable and efficient nanostructured p-type N-doped ZnO photocatalyst for environmentally benign solar hydrogen production - Bhirud, Ashwini P.; Sathaye, Shivaram D.; Waichal, Rupali P.; Nikam, Latesh K.; Kale, Bharat B. (Green Chemistry, 2012)
We have investigated an economical green route for the synthesis of a p-type N-doped ZnO photocatalyst by a wet chemical method. Significantly, hazardous H2S waste was converted into eco-friendly hydrogen energy using the p-type N-doped ZnO photocatalyst under solar light, which has previously been unattempted. The as-synthesized p-type N-doped ZnO shows a hexagonal wurtzite structure. The optical study shows a drastic shift in the band gap of the doped ZnO in the visible region (3.19-2.3 eV). The doping of nitrogen into the ZnO lattice is conclusively proved from X-ray photoelectron spectroscopy analysis and Raman scattering. The morphological features of the N-doped ZnO are studied from FESEM, TEM and reveal particle sizes to be in the range of similar to 4-5 nm. The N-doped ZnO exhibits enhanced photocatalytic hydrogen generation (similar to 3957 mu mol h(-1)) by photodecomposition of hydrogen sulfide under visible light irradiation, which is much higher as compared to semiconductor metal oxides reported so far. It is noteworthy that a green catalyst is investigated to curtail H2S pollution along with production of hydrogen (green fuel) using solar light, i.e., a renewable energy source. The green process investigated will have the potential to synthesize other N-doped metal oxides.

Morphology controlled synthesis of LiV(2)0(5)/Ag nanocomposite nanotubes with enhanced electrochemical performance - Diggikar, Rahul S.; Dhavale, Vishal M.; Shinde, Dhanraj B.; Kanbargi, Nihal S.; Kulkarni, Milind V.; Kale, Bharat B. (RSC Advances, 2012)
Uniformly embedded silver (Ag) nanoparticles in orthorhombic nanotubes (NTs) of lithium vanadium oxide (LVO) synthesized via a facile template-free hydrothermal treatment at low temperature exhibited an excellent morphology with good crystallinity and may act as an exceptional contender for electronic applications.

Nanowires of silver-polyaniline nanocomposite synthesized via in situ polymerization and its novel functionality as an antibacterial agent - Tamboli, Mohaseen S.; Kulkarni, Milind V.; Patil, Rajendra H.; Gade, Wasudeo N.; Navale, Shalaka C.; Kale, Bharat B. (Colloids and Surfaces B-Biointerfaces, 2012)
Silver-polyaniline (Ag-PANI) nanocomposite was synthesized by in situ polymerization method using ammonium persulfate CAPS) as an oxidizing agent in the presence of dodecylbenzene sulfonic acid (DBSA) and silver nitrate (AgNO3). The as synthesized Ag-PANI nanocomposite was characterized by using different analytical techniques such as UV-visible (UV-vis) and Fourier transform Infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FE-SEM), thermo gravimetric analysis (TGA). X-ray diffraction (XRD), and transmission electron microscopy (TEM). UV-visible spectra of the synthesized nanocomposite showed a sharp peak at similar to 420 nm corresponding to the surface plasmon resonance (SPR) of the silver nanoparticles (AgNPs) embedded in the polymer matrix which is overlapped by the polaronic peak of polyaniline appearing at that wavelength. Nanowires of Ag-PANI nanocomposite with diameter 50-70 nm were observed in FE-SEM and TEM. TGA has indicated an enhanced thermal stability of nanocomposite as compared to that of pure polymer. The Ag-PANI nanocomposite has shown an antibacterial activity against model organisms, a gram positive Bacillus subtilis NCIM 6633 in Mueller-Hinton (MH) medium, which is hitherto unattempted. The Ag-PANI nanocomposite with monodispersed AgNPs is considered to have potential applications in sensors, catalysis, batteries and electronic devices. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Conducting poly(aniline); In situ polymerization; Nanocomposite

Organization of cubic CeO2 nanoparticles on the edges of self assembled tapered ZnO nanorods via a template free one-pot synthesis: significant cathodoluminescence and field emission properties - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Patil, Kashinath R.; Koinkar, Pankaj M.; More, Mahendra A.; Murakami, Ri-ichi (Journal of Materials Chemistry, 2012)
The present investigation explores the controlled architecture of a CeO2-ZnO nanocomposite via a template-free, low temperature, facile single step solvothermal approach. This complex architecture depicts cubic single crystalline CeO2 nanoparticles (size similar to 15 nm) grown on the edges of tapered ZnO nanorods with definite orientations and alignments. The formation of wurtzite ZnO, cubic CeO2 and the coexistence of Ce3+ and Ce4+ on the surface of the CeO2-ZnO nanocomposites are confirmed using various characterization tools. The finding of such unique nanostructures by a facile method is exemplified by a plausible growth mechanism. Surprisingly, the aqueous mediated ultrasonication reaction conferred the formation of crystalline ZnO nanotubes of diameter similar to 50 nm. Spatially resolved cathodoluminescence spectra are obtained by linearly scanning an individual CeO2-ZnO nanorod along its length, which reveals the size-dependent surface effects. Interestingly, such hybrid CeO2-ZnO nanoarchitecture is observed to exhibit enhanced field emission properties, demonstrating better current stability as compared to other ZnO nanostructures. This is attributed mainly to strong surface interactions between the Ce-ionic species and the ZnO nanorods. Herein, a soft-chemical approach is used for the first time to architect a binary oxide nanostructure, which is otherwise accomplished using high temperature techniques, as reported elsewhere. Also, the present work not only gives insight into understanding the hierarchical growth behaviour of the CeO2-ZnO nanocomposite in a solution phase synthetic system, but also provides an efficient route to enhance the field emission performance of ZnO nanostructures, which could be extended to other potential applications, such as chemical sensors, optoelectronic devices and photocatalysts.

Controlled synthesis of aligned Bi2S3 nanowires, sharp apex nanowires and nanobelts with its morphology dependent field emission investigations - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Pandiraj, S.; Khare, Ruchita T.; More, Mahendra A. (Crystengcomm, 2013)
Well-aligned ultra-long Bi2S3 nanowire arrays with three kinds of apex morphology - abruptly sharpened apex, thin belt and flat - have been systematically fabricated on tungsten (W) foil by a facile hydrothermal method. The structural and morphological studies reveal formation of distinct tip morphologies, possessing high aspect ratio, single crystalline nature and growth along the orthorhombic [001] axis. A plausible growth mechanism has been proposed on the basis of observed experimental results. The field emission properties of Bi2S3 nanowires and sharp apex Bi2S3 nanowires are investigated. From the field emission studies, the values of the turn-on field, required to draw emission current density of similar to 0.1 mu A cm(-2), are observed to be similar to 2.01 and 1.21 V mu m(-1) for nanowires and sharp apex nanowires, respectively. Furthermore, ultra-long Bi2S3 nanowires are also grown on the W microtip (brush-like) from which very high emission current density similar to 11 mA cm(-2) has been drawn. These results are helpful for the design, fabrication and optimization of integrated field emitters using 1D nanostructures as cold cathode material.

Environmentally benign enhanced H-2 production from abundant copious waste H2S using size tuneable cubic bismuth (Bi-0) quantum dots-GeO2 glass photocatalyst under solar light - Apte, Sanjay K.; Garaje, Sunil N.; Naik, Sonali D.; Waichal, Rupali P.; Kale, Bharat B. (Green Chemistry, 2013)
Hydrogen sulfide is a copious gas produced in refineries (15-20%) as well as billions of tons produced as a by-product in alkali industries. Selectively, only 5% has been utilised for the Claus process to produce liquid sulfur and it is also well known for its uneconomical and environmental problems. Here, we have demonstrated a significant green approach for conversion of poisonous H2S into H-2 by stable cubic bismuth (Bi-0) quantum dot-glass nanosystems using solar light as the energy source. Previously, metal oxides and sulfides have been demonstrated as solar light photocatalysts. However, a unique bismuth quantum dot-glass nanosystem has been designed where cubic phase bismuth quantum dots of size 1-2 nm are grown in the germanate glass matrix successfully. The presence of bismuth (Bi-0) was confirmed by XRD, Raman, TEM and X-ray photoelectron spectroscopy (XPS). The glass nanosystem shows quantum confinement with variation of the band gap from 2.95-1.51 eV. Considering the broad absorption from visible to near IR, we used this glass nanosystem as a solar light active photocatalyst and hydrogen production with respect to the quantum confinement of bismuth (Bi-0) quantum dots has been demonstrated for the first time. The photocatalytic activity for hydrogen production using glass nano-systems having bismuth quantum dot sizes of 1-2 nm and 3-6 nm was measured under solar light and prima fascia observations revealed that the glass nanosystems with very small quantum dots (1-2 nm) showed enhanced hydrogen evolution (11 541 mu mol h(-1) g(-1)) from H2S. The hydrogen evolution obtained is much higher than for previously reported visible light active nanostructured sulfide/oxide or embedded glass nanosystems. The glass nanosystems were also used for water splitting and show evolution of hydrogen without any co-catalyst. It is noteworthy that the quantum dot-glass photocatalyst is highly stable and catalyst regeneration is quite easy and fast. Hence, the QD-bismuth-glass nanocomposites have significant advantages over normal nanosized powder catalysts. Such unique glass nanosystems will also have great potential in photonics and optoelectronic applications.

Quantum confinement controlled solar hydrogen production from hydrogen sulfide using a highly stable CdS0.5Se0.5/CdSe quantum dot-glass nanosystem - Apte, Sanjay K.; Garaje, Sunil N.; Naik, Sonali D.; Waichal, Rupali P.; Baeg, Jin-Ook; Kale, Bharat B. (Nanoscale, 2014)
We have demonstrated unique CdS0.5Se0.5 and CdSe quantum dot-glass nanosystems with quantum confinement effect. The stable, monodispersed CdS0.5Se0.5 and CdSe quantum dots (QDs) of size 2 to 12 nm have been grown in a germanate glass matrix by a simple melt quench technique at moderate temperature. XRD and Raman studies show formation of hexagonal CdS0.5Se0.5 and CdSe in the glass matrix. The quantum confinement of CdS0.5Se0.5 and CdSe was studied using TEM and UV-Vis spectroscopy. The band gap of the glass nanosystem was tuned from 3.6 to 1.8 eV by controlling the CdS0.5Se0.5 quantum dot size in the glass matrix. It can be further tuned to 1.68 eV using growth of CdSe quantum dots in the glass matrix. Considering the tuneable band gap of the CdS0.5Se0.5 and CdSe quantum dot-glass nanosystem for the visible light absorption, a study of size tuneable photocatalytic activity for hydrogen generation from hydrogen sulfide splitting was performed under visible light irradiation for the first time. The utmost hydrogen evolution, i.e. 8164.53 and 7257.36 mu mol h(-1) g(-1) was obtained for the CdS0.5Se0.5 and CdSe quantum dot-glass nanosystems, respectively. The apparent quantum yield (AQY) was observed to be 26% and 21% for the CdS0.5Se0.5 and CdSe quantum dot-glass nanosystems, respectively. It is noteworthy that the present glass nanosystem as a photocatalyst was found to be very stable as compared to naked powder photocatalysts.

Unusual morphologies of reduced graphene oxide and polyaniline nanofibers-reduced graphene oxide composites for high performance supercapacitor applications - Diggikar, Rahul S.; Late, Dattatray J.; Kale, Bharat B. (RSC Advances, 2014)
Herein, we have demonstrated the nanostructured rose flowers, sheets, rods and ferns of reduced graphene oxide by using oxalic acid as a reducing agent. The various morphologies of reduced graphene oxide were obtained by time dependent reduction of graphene oxide. The composites of reduced graphene oxide based polyaniline nanofibers, flower bouquet, and honeycombs were grown at a moderate temperature (60 degrees C) by in situ polymerization of aniline. The structural characterization of composites was performed by using X-ray diffraction, and the existence of reduced graphene oxide in different size, shape and thickness was confirmed by Raman spectroscopy and transmission electron microscopy study. The electrochemical study of reduced graphene oxides and their composites with polyaniline nanostructures was performed. The composite of honeycomb reduced graphene oxide-polyaniline nanofibers showed enhancement in the electrochemical performance (specific capacitance: 470 F g(-1)) compared to earlier reports. Such type of composites will be a potential contender for super capacitors.

Decoration of CdS nanoparticles on 3D self-assembled ZnO nanorods: a single-step process with enhanced field emission behaviour - Warule, Sambhaji S.; Chaudhari, Nilima S.; Shisode, Raju T.; Desa, Keith V.; Kale, Bharat B.; More, Mahendra A. (CrystEngComm, 2015)
A well-defined CdS-ZnO heteroarchitecture has been synthesized via a facile single-step hydrothermal approach. The morphological and structural studies reveal the formation of 3D nano-architectures, in which self-assembled ZnO nanorods (diameter similar to 50 nm) are well decorated with single crystalline CdS nanoparticles (size similar to 10 nm). The CdS-ZnO heteroarchitecture exhibits a remarkable change in the optical absorption due to the surface modification of ZnO nanorods by CdS. Surprisingly, under identical reaction conditions, the global ZnS nanoparticles are selectively grown at the apex of ZnO nanorods on the Zn substrate. Furthermore, a plausible growth mechanism has been presented on the basis of experimental results. Interestingly, the CdS-ZnO heteroarchitecture shows enhanced field emission properties such as low turn-on field, high emission current density and better current stability in comparison to other ZnO-based nanostructures. The present CdS-ZnO heteroarchitecture could be extended to other potential applications, such as chemical sensors, photodetectors, optoelectronic devices, and photocatalysts.

Hierarchical CdS nanostructure by Lawesson's reagent and its enhanced photocatalytic hydrogen production - Pandit, Vikram U.; Arbuj, Sudhir S.; Hawaldar, Ranjit R.; Kshirsagar, Pradnya V.; Deshmukh, Amarsinh J.; Ambekar, Jalindar D.; Mulik, Uttam P.; Gosavi, Suresh W.; Kale, Bharat B. (RSC Advances, 2015)
Lawesson's reagent (LR) has been effectively exploited for the synthesis of hierarchical architectures of cadmium sulphide (CdS) nanostructures for the first time. The X-ray diffractograms of the as synthesised CdS nanostructures confirm the formation of hexagonal CdS. The broadness of the XRD peaks clearly indicates the nanocrystalline nature of CdS with average crystallite size of 4 nm. A FESEM study revealed the formation of hierarchical nanostructures, whereas a TEM study showed that the hierarchical arrangement is composed of nanosized CdS particles. A band-gap i.e. 2.4 eV was derived from diffuse reflectance spectroscopy. The photoluminescence spectrum showed an emission peak at 535 and 568 nm which can be attributed to band-edge emission and surface emissions or possible metal vacancies, respectively. Considering the band-gap within the visible region, the photocatalytic hydrogen evolution performance of these CdS nanostructures was performed under visible light irradiation from hydrogen sulphide and water, respectively. Utmost hydrogen evolution i.e. 14 136 mu mol h(-1) g(-1) and 2065 mu mol h(-1) g(-1) was observed over a naked CdS nanostructure via H2S and water decomposition, respectively. The amount of hydrogen obtained by H2S splitting is much higher as compared to earlier reports.

Nanostructured 2D MoS2 honeycomb and hierarchical 3D CdMoS4 marigold nanoflowers for hydrogen production under solar light - Kadam, Sunil R.; Late, Dattatray J.; Panmand, Rajendra P.; Kulkarni, Milind V.; Nikam, Latesh K.; Gosavi, Suresh W.; Park, Chan J.; Kale, Bharat B. (Journal of Materials Chemistry A, 2015)
Unique two dimensional (2D) honeycomb layered MoS2 nanostructures and hierarchical 3D marigold nanoflowers of CdMoS4 were designed using a template free and facile solvothermal method. The MoS2 structure is depicted with a sheet like morphology with lateral dimensions of 5-10 mu m and a thickness of similar to 200 nm and a honeycomb nanostructure architecture produced via the self-assembling of vertically grown thin hexagonal nanosheets with a thickness of 2-3 nm. The 3D CdMoS4 marigold nanoflower architecture comprised thin nanopetals with lateral dimensions of 1-2 mu m and a thickness of a few nm. The CdMoS4 and MoS2 structures displayed hydrogen ( H-2) production rates of 25 445 and 12 555 mu mol h(-1) g(-1), respectively. The apparent quantum yields of hydrogen production were observed to be 35.34% and 17.18% for CdMoS4 and MoS2, respectively. The 3D nanostructured marigold flowers of CdMoS4 and honeycomb like 2D nanostructure of MoS2 were responsible for higher photocatalytic activity due to inhibition of the charge carrier recombination. The prima facie observation of H-2 production showed that the ternary semiconductor confers enhanced photocatalytic activity for H-2 generation due to its unique structure. Such structures can be designed and implemented in other transition metal dichalcogenide based ternary materials for enhanced photocatalytic and other applications.

Situ preparation of N-TiO2/graphene nanocomposite and its enhanced photocatalytic hydrogen production by H2S splitting under solar light - Bhirud, Ashwini P.; Sathaye, Shivaram D.; Waichal, Rupali P.; Ambekar, Jalindar D.; Park, Chan-J.; Kale, Bharat B. (Nanoscale, 2015)
Highly monodispersed nitrogen doped TiO2 nanoparticles were successfully deposited on graphene (N-TiO2/Gr) by a facile in-situ wet chemical method for the first time. N-TiO2/Gr has been further used for photocatalytic hydrogen production using a naturally occurring abundant source of energy i.e. solar light. The N-TiO2/Gr nanocomposite composition was optimized by varying the concentrations of dopant nitrogen and graphene (using various concentrations of graphene) for utmost hydrogen production. The structural, optical and morphological aspects of nanocomposites were studied using XRD, UV-DRS, Raman, XPS, FESEM, and TEM. The structural study of the nanocomposite shows existence of anatase N-TiO2. Further, the details of the components present in the composition were confirmed with Raman and XPS. The morphological study shows that very tiny, 7-10 nm sized, N-TiO2 nanoparticles are deposited on the graphene sheet. The optical study reveals a drastic change in absorption edge and consequent total absorption due to nitrogen doping and presence of graphene. Considering the extended absorption edge to the visible region, these nanocomposites were further used as a photocatalyst to transform hazardous H2S waste into eco-friendly hydrogen using solar light. The N-TiO2/Gr nanocomposite with 2% graphene exhibits enhanced photocatalytic stable hydrogen production i.e. similar to 5941 mu mol h(-1) under solar light irradiation using just 0.2 gm nanocomposite, which is much higher as compared to P25, undoped TiO2 and TiO2/Gr nanocomposite. The enhancement in the photocatalytic activity is attributed to `N' doping as well as high specific surface area and charge carrier ability of graphene. The recycling of the photocatalyst shows a good stability of the nanocomposites. This work may provide new insights to design other semiconductor deposited graphene novel nanocomposites as a visible light active photocatalyst.

Architecture of 2D MoS2 nanosheets and 3D CdMoS4 marigold flowers: consequence of annealing on field emission performance - Kadam, Sunil R.; Suryawanshi, Sachin R.; Panmand, Rajendra P.; Mate, Vivek R.; More, Mahendra A.; Late, Dattatray J.; Kale, Bharat B. (Microporous and Mesoporous Materials, 2016)
Herein, we report the field electron emission investigations on template free solvothermally synthesized layered MoS2 nanosheets as well as novel phase of CdMoS4 nanoflowers at the base pressure of similar to 1 x 10(-8) mbar. The turn-on field, threshold field and maximum emission current densities for both MoS2 and CdMoS4 are strongly influenced by thermal annealing in inert atmosphere. The turn on field, required to draw emission current density of 1 mu A/cm(2) is found to be 5.8 and 3.2 V/mu m for pristine and annealed MoS2 at 400 degrees C. In case of as prepared and annealed CdMoS4 sample the turn on field values are found to be similar to 6.2 and 5.0 V/mu m, respectively. The emission current versus time (I-t) plot measured at the preset current values of similar to 1 mu A for pristine and annealed sample indicates stable operation of the emitter. The emission current fluctuations for annealed sample are observed to be less as compared with the pristine sample due to conditioning of the emitter, thereby showing highly stable nature of emitter. Thus, the present result demonstrates the potential of annealed MoS2 nanosheets and CdMoS4 nanoflowers as an emerging materials for micro/nanoelectronics and flat panel field emission display applications. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: field emission; MoS2 and CdMoS4; Nanoflowers; nanosheets

In situ fabrication of highly crystalline CdS decorated Bi2S3 nanowires (nano-heterostructure) for visible light photocatalyst application - Panmand, Rajendra P.; Sethi, Yogesh A.; Deokar, Rajashree S.; Late, Dattatray J.; Gholap, Haribhau M.; Baeg, Jin-Ook; Kale, Bharat B. (RSC Advances, 2016)
In situ synthesis of the orthorhombic Bi2S3 nanowires decorated with hexagonal CdS nanoparticles (nano-heterostructure) has been demonstrated by a facile solvothermal method. The tiny 5-7 nm CdS spherical nanoparticles are decorated on the surfaces of 30-40 nm Bi2S3 nanowires, successfully. Structural, morphological and optical studies clearly show the existence of CdS on the nanowires. A possible sequential deposition growth mechanism is proposed on the basis of experimental results to reveal the formation of the nano heterostructure. The heterostructures have been used as a photocatalyst for hydrogen production as well as degradation of methylene blue under solar light. The maximum hydrogen evolution i.e. 4560 and 2340 mu mol h(-1) 0.5 g was obtained from H2S splitting and glycerol degradation for Bi2S3 NWs decorated with CdS nanoparticles (nano-heterostructure) which is higher than that of the Bi2S3 NWs (3000 and 1170 mu mol h(-1) 0.5 g, respectively). The enhanced photocatalytical hydrogen evolution efficiency of the heterostructures is mainly attributed to its nanostructure. In the nano heterostructure, the CdS nanoparticles control the charge carrier transition, recombination, and separation, while the Bi2S3 nanowire serves as a support for the CdS nanoparticles. The photogenerated electron's migration is faster than the holes from the inside of a CdS nanoparticle to its surface or to the phase interface, resulting in a relatively higher hole density inside the CdS nanoparticle leaving electron density at surface of the Bi2S3 NWs. This influences the photocatalytic activity under solar light. Such nano-heterostructures may have potential in other photocatalytic reactions.

Situ fabrication of highly crystalline CdS decorated Bi2S3 nanowires (nano-heterostructure) for visible light photocatalyst application - Panmand, Rajendra P.; Sethi, Yogesh A.; Deokar, Rajashree S.; Late, Dattatray J.; Gholap, Haribhau M.; Baeg, Jin-Ook; Kale, Bharat B. (RSC Advances, 2016)
In situ synthesis of the orthorhombic Bi2S3 nanowires decorated with hexagonal CdS nanoparticles (nano-heterostructure) has been demonstrated by a facile solvothermal method. The tiny 5-7 nm CdS spherical nanoparticles are decorated on the surfaces of 30-40 nm Bi2S3 nanowires, successfully. Structural, morphological and optical studies clearly show the existence of CdS on the nanowires. A possible sequential deposition growth mechanism is proposed on the basis of experimental results to reveal the formation of the nano heterostructure. The heterostructures have been used as a photocatalyst for hydrogen production as well as degradation of methylene blue under solar light. The maximum hydrogen evolution i.e. 4560 and 2340 mu mol h(-1) 0.5 g was obtained from H2S splitting and glycerol degradation for Bi2S3 NWs decorated with CdS nanoparticles (nano-heterostructure) which is higher than that of the Bi2S3 NWs (3000 and 1170 mu mol h(-1) 0.5 g, respectively). The enhanced photocatalytical hydrogen evolution efficiency of the heterostructures is mainly attributed to its nanostructure. In the nano heterostructure, the CdS nanoparticles control the charge carrier transition, recombination, and separation, while the Bi2S3 nanowire serves as a support for the CdS nanoparticles. The photogenerated electron's migration is faster than the holes from the inside of a CdS nanoparticle to its surface or to the phase interface, resulting in a relatively higher hole density inside the CdS nanoparticle leaving electron density at surface of the Bi2S3 NWs. This influences the photocatalytic activity under solar light. Such nano-heterostructures may have potential in other photocatalytic reactions.

Facile synthesis of unique cellulose triacetate based flexible and high performance gel polymer electrolyte for lithium ion batteries - Nirmale, Trupti C.; Karbhal, Indrapal; Kalubarme, Ramchandra S.; Shelke, Manjusha V.; Varma, Anjani J.; Kale, Bharat B. (ACS Applied Materials & Interfaces, 2017)
Lithium ion batteries (LIBs) with polymer based electrolytes have attracted enormous attention due to the possibility of fabricating intrinsically safer and flexible devices. However, economical and eco-friendly sustainable technology is an oncoming challenge to fulfill the ever increasing demand. To circumvent this issue, we have developed a gel polymer electrolyte (GPE) based on renewable polymers like cellulose triacetate and poly (polyethylene glycol methacrylate) p(PEGMA) using a photo polymerization technique. Cellulose triacetate offers good mechanical strength with improved ionic conductivity, owing to its ether and carbonyl functional groups. It is observed that the presence of an open network has a critical impact on lithium ion transport. At room temperature, GPE PC exhibits an optimal ionic conductivity of 1.8 x 10(-3) S cm(-1) and transference number of 0.7. Interestingly, it affords an excellent electrochemical stability window up to 5.0 V vs Li/Li+. GPE PC shows a discharge capacity of 164 mAhg(-1) after the first cycle when evaluated in a Li/GPE/LiFePO4 cell at 0.5 C-rate. Interfacial compatibility of GPE PC with lithium metal improves the overall cycling performance. This system provides a guiding principle toward a future renewable and flexible electrolyte design for flexible LIBs (FLIBs).

Review on cellulose and lignin based binders and electrodes: Small steps towards a sustainable lithium ion battery - Nirmale, Trupti C.; Kale, Bharat B.; Varma, Anjani J. (International Journal of Biological Macromolecules, 2017)
Lithium ion batteries (LIB) are the most promising energy storage systems for portable electronics and future electric or hybrid-electric vehicles. However making them safer, cost effective and environment friendly is the key challenge. In this regard, replacing petro-derived materials by introducing renewable biomass derived cellulose derivatives and lignin based materials into the battery system is a promising approach for the development of green materials for LIB. These biomaterials introduce sustainability as well as improved safety in the final disposal of LIB batteries. In this review we introduce LIB materials technology in brief and recent developments in electrodes and binders based on cellulose and their derivatives and lignin for lithium ion batteries. (C) 2017 Elsevier B.V. All rights reserved.

Facilitated lithium storage in hierarchical microsphere of Cu2S-MoS2 ultrathin nanosheets - Kadam, Sunil R.; Kalubarme, Ramchandra S.; Deshmukh, Shrutika P.; Panmand, Rajendra P.; Kawade, Ujjwala, V.; Kulkarni, Milind, V.; Deo, Shriniwas S.; Gosavi, Suresh W.; Kale, Bharat B. (ChemistrySelect, 2018)
Considering the high energy density Lithium ion batteries have become one of the best option for next-generation energystorage technologies. Transition metal chalcogenide nanomaterials are promising electrodes for Lithium-ion batteries. Molybdenum based layered chalcogenide materials wisely studied for rechargeable Li-ion batteries, due to its two-dimensional (2D) layered structure and better specific capacity. The three-dimensional (3D) synthesis of microsphere by ultrathin nanosheets is necessary for practical applications. Herein, the fabrication of a unique hierarchical 2D layered Cu2S-MoS2 nanostructure was (ultrathin nanosheets) demonstrated via in situ assembling of two-dimensional (2D) growths in facile solvothermal technique. The structural study reveals the existence of Cubic Cu2S and Rhombohedral MoS2 phase. Morphological study by FESEM and TEM shows unique ultrathin nanosheets of similar to 10 nm thickness self-assembled in the form of layered microsphere. In Li- ion storage testing, Cu2S-MoS2 electrode exhibited good specific discharge capacity of 651 mAhg(-1) at 50 mAg(-1) applied current and maintained 320 mAhg(-1) after 100 cycles. The facilitated advanced electrochemical performance attributed to layered ultrathin Cu2S-MoS2 composite nanosheets.

Architecture of NaFe(MoO4)2 as a novel anode material for rechargeable lithium and sodium ion batteries - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Praveen, C. S.; Dwivedi, Pravin Kumari; Karbhal, Indrapal; Gosavi, Suresh W.; Shelke, V, Manjusha; Kale, Bharat B. (Applied Surface Science, 2021)
In recent decades, particular focus has been given to enhance the capacity of LIBs and SIBs either by developing new materials or by modifying existing materials. Hence, we have demonstrated a new anode material i.e. sodium iron molybdate [NaFe(MoO4)2] for both LIBs and SIBs. NaFe(MoO4)2 has been successfully synthesized by solid-state combustion technique and tested as a promising new anode material for both LIBs and SIBs. A detailed analysis of the crystal structure has been performed using DFT calculations. NaFe(MoO4)2 crystallizes in the monoclinic phase with the space group C2/c (#15). FESEM also shows highly crystalline monoclinic shaped crystals of micron size. When evaluated as an anode material for LIBs, NaFe(MoO4)2 electrode exhibited electrochemical capacity of 920 mAhg- 1 in the second cycle at the current density of 50 mAg-1. Though capacity decreases on further cycling, the coulombic efficiency was maintained at 99% for 50 cycles. Significantly, a high discharge capacity of 100 mAhg- 1 was maintained at a very high rate of 1 Ag-1. On the other hand, we have also tested NaFe(MoO4)2 for SIBs which shows excellent reversible specific capacity i.e. 100 mAhg- 1 at the current density of 100 mAg-1 even after 500 cycles. This novel system has shown good stability for LIBs and SIBs which is hitherto unattempted.
Keywords: Electrochemical study; lithium-ion battery; Morphology; NaFe(MoO4)2; Sodium-ion battery

Engineering microstructure of LiFe(MoO4)(2) as an advanced anode material for rechargeable lithium-ion battery - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Dwivedi, Pravin Kumari; Praveen, C. S.; Karbhal, Indrapal; Shelke, V, Manjusha; Kim, Bomyung; Park, Chinho; Kale, Bharat B. (Journal of Materials Science-Materials In Electronics, 2021)
Graphite is considered as an ideal anode material for lithium-ion battery (LIB) due to its high stability, good conductivity and wide source of availability. However, the low energy density and theoretical capacity of graphite cannot meet the needs of high performance anode materials. To circumvent this issue, alternative materials have been sought for many years now. Herein, we report the synthesis of highly crystalline lithium iron molybdate LiFe(MoO4)(2) by combustion method and evaluated its performance as an anode material for lithium-ion batteries. Triclinic LiFe(MoO4)(2) crystals having particle size 2-5 mu m with good crystallinity were obtained. The material shows long cycle life and high rate performance than commercial graphite and exhibits first reversible discharge capacity of 931.6 mAh/g at a current density of 100 mA/g which is three times higher than commercial graphite. The high specific capacity together with the outstanding rate and cycle performance makes LiFe(MoO4)(2) a promising anode material for LIB. A detailed analysis on the crystal structure and electronic properties of LiFe(MoO4)(2) is presented based on DFT studies to complement the experimental observations.

MoS2 and CdMoS4 nanostructure-based UV light photodetectors - Pawar, Mahendra S.; Kadam, Sunil R.; Kale, Bharat B.; Late, Dattatray J. (Nanoscale Advances, 2021)
We have developed MoS2 nanosheets and CdMoS4 hierarchical nanostructures based on a UV light photodetector. The surface morphologies of the as-prepared samples were investigated via field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). The performance parameters for the present photodetectors are investigated under the illumination of UV light having a wavelength of similar to 385 nm. Upon the illumination of UV light, the CdMoS4-based photodetector device showed a better response to UV light compared to the MoS2 device in terms of photoresponsivity, response time (similar to 72 s) and recovery time (similar to 94 s). Our results reveal that CdMoS4 hierarchical nanostructures are practical for enhancing the device performance.